A mixed-dimensional WS2/GaSb heterojunction for high-performance p–n diodes and junction field-effect transistors. Issue 4 (11th January 2022) - Cheng, Zichao; Song, Xiufeng; Jiang, Lianfu; Wang, Lude; Sun, Jiamin; Yang, Zaixing; Jian, Yuxuan; Zhang, Shengli; Chen, Xiang; Zeng, Haibo
Abstract : High-performance WS2 /GaSb junction field-effect transistor. Abstract : GaSb nanowires integrated on a silicon-based substrate are of great significance for p-type field-effect transistors. In particular, chips are becoming more and more miniaturized, and complicated dielectric engineering needs to be avoided. Therefore, the introduction of junction field-effect transistor (JFET) can be used to improve the performance of transistors. We demonstrated a heterostructure p-channel depletion type GaSb junction field-effect transistor by combining with n-WS2 sheets. Typical diode characteristics are observed in n-WS2 /p-GaSb heterostructure diodes, with a high rectification ratio of ∼10 4 . The JFET has excellent electrical features with an ON/OFF ratio of ∼10 4 and the sub-threshold swing (SS ≈ 723 mV dec −1 ). With the back gate control the ON/OFF current ratio is improved to ∼10 6 and the low SS is restrained to 166 mV dec −1 . Moreover, due to the electrical properties of the heterojunction the JFET and p–n diodes maintain good stability at high temperatures. Therefore, the WS2 /GaSb heterojunction enables the miniaturization of an integrated power electronic system and provides a promising route to low power electronics.